Impact of Smoking Status on Stroke Recurrence. Issue 8 (16th April 2019) - Chen, Jingjing; Li, Shun; Zheng, Kuo; Wang, Huaiming; Xie, Yi; Xu, Pengfei; Dai, Zhengze; Gu, Mengmeng; Xia, Yaqian; Zhao, Min; Liu, Xinfeng; Xu, Gelin
Abstract : Background: Smoking is a well‐established risk factor of stroke and smoking cessation has been recommended for stroke prevention; however, the impact of smoking status on stroke recurrence has not been well studied to date. Methods and Results: Patients with first‐ever stroke were enrolled and followed in the NSRP (Nanjing Stroke Registry Program). Smoking status was assessed at baseline and reassessed at the first follow‐up. The primary end point was defined as fatal or nonfatal recurrent stroke after 3 months of the index stroke. The association between smoking and the risk of stroke recurrence was analyzed with multivariate Cox regression model. At baseline, among 3069 patients included, 1331 (43.4%) were nonsmokers, 263 (8.6%) were former smokers, and 1475 (48.0%) were current smokers. At the first follow‐up, 908 (61.6%) patients quit smoking. After a mean follow‐up of 2.4±1.2 years, 293 (9.5%) patients had stroke recurrence. With nonsmokers as the reference, the adjusted hazard ratios for stroke recurrence were 1.16 (95% CI, 0.75–1.79) in former smokers, 1.31 (95% CI, 0.99–1.75) in quitters, and 1.93 (95% CI, 1.43–2.61) in persistent smokers. Among persistent smokers, hazard ratios for stroke recurrence ranged from 1.68 (95% CI, 1.14–2.48) in those who smoked 1 to 20 cigarettes daily to 2.72 (95% CI, 1.36–5.43) in those who smoked more than 40 cigarettes daily ( P for trend <0.001). Conclusions: After an initial stroke, persistent smoking increases the risk of stroke recurrence. There exists a dose–response relationship between smoking quantity and the risk of stroke recurrence.